(untitled) (Research, Society and Development, 2022)
This study aimed to identify the epidemiological profile of confirmed cases and deaths from COVID-19 reported in Munhoz de Mello-Paraná, in the years 2020 and 2021. This is a descriptive study, with a quantitative approach, carried out from the analysis of confirmed cases and deaths by COVID-19 notified from January 1, 2020 to December 31, 2021, in Munhoz de Mello-PR. The data were extracted from the COVID-19 Notify System, under the domain of the Epidemiological Surveillance of that municipality. After collection, the data were analyzed in absolute and relative frequency for an exploratory analysis. In the investigated period, 538 cases of COVID-19 were reported with the highest incidence in March 2021 (18.02%). There was a prevalence of females (54.27%) and the age group most affected was between 21 and 40 years old (40.88%). The most common symptoms were cough (50.37%), headache (47.95%) and myalgia (40.52%), with emphasis on the comorbidities hypertension (9.66%) and diabetes (4.83%) existing. Nine deaths (1.67%) were reported and of these, 55.55% were women and 77.77% were in individuals aged 61 years or older. The findings of this study revealed the epidemiological profile of confirmed COVID-19 cases and deaths in the field of study and suggest that economically active women were more affected by SARSCoV-2. Regarding deaths, an incidence of one death was identified for every 59 confirmed cases, most of them in elderly women, with comorbidity and need for hospitalization.